Chemometric Study of Trace Elements in Hard Coals of the Upper Silesian Coal Basin, Poland. (22nd May 2014) - Smoliński, Adam; Rompalski, Przemysław; Cybulski, Krzysztof; Chećko, Jarosław; Howaniec, Natalia
Abstract : The objective of the study was the analysis of trace elements contents in coals of the Upper Silesian Coal Basin (USCB), which may pose a potential threat to the environment when emitted from coal processing systems. Productive carbon overburden in central and southern zones of the USCB is composed mostly of insulating tertiary formations of a thickness from a few m to 1, 100 m, and is represented by Miocene and Pliocene formations. In the data study the geological conditions of the coal seams of particular zones of the USCB were taken into account and the hierarchical clustering analysis was applied, which enabled the exploration of the dissimilarities between coal samples of various zones of the USCB in terms of basic physical and chemical parameters and trace elements contents. Coals of the northern and eastern zones of the USCB are characterized by high average Hg and low average Ba, Cr, and Ni contents, whereas coals of southern and western zones are unique due to high average concentrations of Ba, Co, Cu, Ni, and V. Coals of the central part of the USCB are characterized by the highest average concentration of Mn and the lowest average concentrations of As, Cd, Pb, V, and Zn.